Cervical, anal and oral human papillomavirus (HPV) infection in young women: A case control study between women with perinatally HIV infection and women with non-perinatally HIV infection. (January 2020) - Gilles, Christine; Buljubasic, Marie; Konopnicki, Déborah; Manigart, Yannick; Barlow, Patricia; Rozenberg, Serge
Abstract: Objectives: HPV infection may differ in women who are HIV-positive since birth (perinatally infected, P-HIV) and those who acquire HIV later in life (non-perinatally infected, NP-HIV). We assessed the HPV prevalence in relation to the HIV acquisition route and HPV vaccination status. Study design: Case control study comparing 22 P-HIV with 22 NP-HIV patients. Cervical, anal and oral specimen were collected for HPV PCRs. The primary outcome was the prevalence of cervical, oral and anal HPV in P-HIV and NP-HIV patients. The secondary outcome was to identify risk factors for HPV infection. Comparative statistics for two independent groups, univariate and multivariable logistic regression analyses were used. Results: There were no differences between perinatally and non-perinatally infected women. Cervical dysplasia was found in 12/44 (27 %) patients and high-risk HPV (hrHPV) in 30 % of cervical (of which 89 % were hrHPV other than 16 and 18), in 3 % of oral and 65 % of anal specimens. All woman were using combined antiretroviral therapy (cART) and 64 % had HIVRNA < 20 cp/ml. A CD4 count <350/mm³ was associated with cytological abnormalities (OR: 13.52, p = 0.002) and with cervical HPV (OR: 6.11; p = 0.04); anal HPV was associated with a previous cervical dysplasia and concomitant cervical HPV infection. None of thirteen vaccinated patients had a 6/11/16/18 HPV infection. Conclusion: In this small series of women under cART, we did not observe a difference in HPV infection in relation to the route of HIV acquisition. The high prevalence of hrHPV other than 16 and 18 support the use of a 9-valent vaccine.